Communicated Accountability Of Charitable Organisations: The Case Of Nigeria - Musawa, Mubarak Shehu (Fakultas Ekonomi dan Bisnis, UNTAN, 2019)
The aim of this study is to examine how accountability is practised by charity institutions in Nigeria.The paper employs Ebrahim